2011
DOI: 10.1071/an10112
|View full text |Cite|
|
Sign up to set email alerts
|

Relationship between litter birthweight and litter size in five goat genotypes

Abstract: The aim of the present study was to use a non-linear regression approach to investigate the relationship between litter birthweight and litter size of five breeds of goat under intensive conditions in a hot arid environment. Litter-size and litter-weight data on 20 117 kids from 13 685 litters representing five breeds, namely Saanen, Toggenburg, French Alpine, Anglo-Nubian and Granadina, were compared to evaluate this relationship. Regardless of breed, birthweight for kids born as twins, triplets and quadruple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
4
8
0
1
Order By: Relevance
“…The overall mean of litter size was 1.51±0.50, ranged between 1-3 and variation 33.65% (Table 1). This result was in agreement of some literature stated that litter size of goats ranged between 1-1.7 (Sutama et al 2011;Mellado et al 2011;Parasmawati et al 2013).…”
Section: Reproductive Characteristicssupporting
confidence: 82%
See 1 more Smart Citation
“…The overall mean of litter size was 1.51±0.50, ranged between 1-3 and variation 33.65% (Table 1). This result was in agreement of some literature stated that litter size of goats ranged between 1-1.7 (Sutama et al 2011;Mellado et al 2011;Parasmawati et al 2013).…”
Section: Reproductive Characteristicssupporting
confidence: 82%
“…This results were similar to some findings that litter size were not affected by genotypes or breed of local goats in Ethiopia (Dereje et al 2015) and PE goats (Parasmawati et al 2013). In Mexico, Anglo Nubian showed litter size 1.56±0.5 (Mellado et al 2011) similar to this present study. Other study mentioned that Anglo Nubian, in Sudan, showed litter size of 1.75±0.71 (Hassna et al 2013) higher than this study.…”
Section: Genotype Effectssupporting
confidence: 80%
“….6 ± 12.9 a 77.7 ± 9.14 a 80.9 ± 9.04 a 88.5 ± 3.03 a as possible consequence of the fact that dietary requirements of primiparous goats included a portion for weight gain (to reach the adult weight) in addition to those for maintenance and development of the fetuses during late pregnancy or those for maintenance and milk synthesis during early lactation (Pulina and Cannas, 2008). Saanen goats give birth to 1.34 ± 0.52 and 1.46 ± 0.58 kids for primiparous and multiparous goats, respectively (Mellado et al, 2011). We report a greater number of kids per dam that appears not to have affected fetus development.…”
Section: Mean Dmi Litter Size Kid Bw Goat Bw and Milk Yieldmentioning
confidence: 57%
“…This Saanen breed was introduced in to breeding program of the Indonesian Research Institute for Animal Production to improve quality and quantity of goat milk yield. This Saanen breed often produced triplets (Mellado et al 2011) and higher milk yield compared to Etawah Grade (Praharani 2014) and Angora goats (Anwar et al 2015). Therefore, Saanen genetics were used to produce a new goat breed with higher milk yield and adapted well to Indonesian environmental conditions.…”
Section: Introductionmentioning
confidence: 99%